2019
DOI: 10.3758/s13423-019-01600-1
|View full text |Cite
|
Sign up to set email alerts
|

Relevance-based processing: Little role for task-relevant expectations

Abstract: This study examined the role of advance expectations in generating relevance-based selection, using a version of cognitive Bblindnesst hat is driven solely by task relevance. With this irrelevance-induced blindness, participants often fail to report a feature of an irrelevant stimulus, even though the levels of perceptual and cognitive load are minimal (i.e., capacity limitations are not met). Hence, with this phenomenon, selection is based solely on task relevance. In two experiments, we examined such relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, it is possible that the small differences in procedure explain the discrepancies between previous findings (Chen & Wyble, 2015;Eitam et al, 2015). Indeed, it has been demonstrated that under different conditions, even foveally presented attributes may not always be reportable on a surprise trial (see, e.g., Chen, Swan, & Wyble, 2016;Eitam et al, 2013;Swan, Collins, & Wyble, 2016;Tapal, Yeshurun, & Eitam, 2019). For instance, in one variant of the surprise paradigm (see Eitam et al, 2013;Wyble, Hess, O'Donnell, Chen, & Eitam, 2019), a disc with a differently colored surrounding ring is presented right at screen center for 500 ms.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is possible that the small differences in procedure explain the discrepancies between previous findings (Chen & Wyble, 2015;Eitam et al, 2015). Indeed, it has been demonstrated that under different conditions, even foveally presented attributes may not always be reportable on a surprise trial (see, e.g., Chen, Swan, & Wyble, 2016;Eitam et al, 2013;Swan, Collins, & Wyble, 2016;Tapal, Yeshurun, & Eitam, 2019). For instance, in one variant of the surprise paradigm (see Eitam et al, 2013;Wyble, Hess, O'Donnell, Chen, & Eitam, 2019), a disc with a differently colored surrounding ring is presented right at screen center for 500 ms.…”
Section: Discussionmentioning
confidence: 98%
“…It is commonly believed that if a person attends to a stimulus then, immediately afterwards, they will be able to report it (Lamme, 2004; Simons & Chabris, 2011). It turns out this intuition is not always correct (H. Chen et al., 2016; H. Chen & Wyble, 2015a; Eitam et al., 2013; Tapal et al., 2019). Attribute amnesia (AA) is a particularly dramatic demonstration of this.…”
mentioning
confidence: 99%